Pengembangan Hypothectial Learning Trajectory Topik Pola Bilangan Berbasis Realistic Mathematic Education - Suryabayu, Eka Pasca; Fauzan, Ahmad; Armiati, Armiati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to produce a Hypothetical Learning Trajectory (HLT) in helping students understand the concept of number patterns. The research method used is design research. The research is focused on designing HLT which is validated, revised and tested one-to-one for students. Research data were collected through observation, interviews, and analysis of student answers. The instruments used are HLT and student worksheets using the Realistic Mathematics Education (RME) approach through literature study. The collected data were collected and analyzed qualitatively. This research was conducted at the Non-Formal Education Program Package A level 2, involving 3 students with high, medium and low ability levels. The results of the analysis show that students with medium and high abilities can understand the material quite well, while students with low abilities have difficulty understanding the problems given.Â Penelitian ini bertujuan untuk menghasilkan Hypothetical Learning Trajectory (HLT) dalam membantu peserta didik dalam memahami konsep pola bilangan. Metode penelitian yang digunakan adalah penelitian desain. Penelitian difokuskan untuk merancang HLT yang divalidasi, direvisi dan diujicobakan secara one-to-one kepada peserta didik. Data penelitian dikumpulkan melalui observasi, wawancara, dan analisis jawaban peserta didik. Instrument yang digunakan berupa HLT dan lembar kerja peserta didik dengan menggunakan pendekatan Realistic Mathematics Education Â (RME) melalui studi literature. Data yang dikumpulkan dikumpulkan dianalisis secara kualitatif. Penelitian ini dilakukan pada Pendidikan Non Formal Program Paket A tingkat 2, dengan melibatkan 3 orang peserta didik dengan tingkat kemampuan tinggi, sedang dan rendah. Hasil analisis menunjukkan bahwaÂ peserta didik dengan kemampuan sedang dan tinggi dapat memahami materi cukup baik, sedangkan peserta didik kemampuan rendah mengalami kesulitan dalam memahami masalah yang diberikan.